2019
DOI: 10.1080/13880209.2019.1651343
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MEG3 attends to morphine-mediated autophagy of HT22 cells through modulating ERK pathway

Abstract: Context: Morphine is an alkaloid isolated from the poppy plants. The addiction of morphine is a very serious social issue. Some long non-coding RNAs (lncRNAs) have been proposed to engage in drug addiction. Objective: Whether lncRNA maternally expressed gene 3 (MEG3) attended to morphine-mediated autophagy of mouse hippocampal neuronal HT22 cells was probed. Materials and methods: HT22 cells were subjected to 10 µM morphine for 24 h. Cell autophagy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…There have been many reports on the functions of lncRNA-Meg3, PDGFRA and miR-421 in tumours, suggesting that these three molecules have very important regulatory effects on tumour proliferation and invasion (35,37,(45)(46)(47)(48)(49)(50)(51)(52). However, there have been no reports discussing the three in combination.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports on the functions of lncRNA-Meg3, PDGFRA and miR-421 in tumours, suggesting that these three molecules have very important regulatory effects on tumour proliferation and invasion (35,37,(45)(46)(47)(48)(49)(50)(51)(52). However, there have been no reports discussing the three in combination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with the morphine + si-MEG3 group, Beclin-1 and LC3-II/LC3-I expression in HT22 cells in the morphine + si-MEG3 + SCH772984 group were further reduced. These experiments indicate that MEG3 upregulation may be involved in the effect of morphine on autophagy in HT22 cells by promoting ERK pathway activation 62 .…”
Section: Lncrna Meg3mentioning
confidence: 73%
“…Although these lncRNAs have not been reported to be involved in drug addiction, dysregulated expression of lncRNAs has been reported to play a critical role in the progression of addiction ( 26 , 27 ). Gao et al showed that upregulation of MEG3 was involved in morphine-induced autophagy in hippocampal neuronal HT22 cells ( 28 ). In addition, analysis of significantly dysregulated miRNAs revealed many downregulated miRNAs, including miR-124 and miR-218, and upregulated miRNAs, including miR-451a and miR-15b-3p, were involved in drug addiction.…”
Section: Discussionmentioning
confidence: 99%